A multi-species reactive transport model based on ion-solid phase interaction for saturated cement-based materials. (September 2022) - Sharmilan, Suntharalingam; Stang, Henrik; Michel, Alexander
Abstract: This study established a reactive transport model (RTM) for saturated cement-based materials based on multi-ionic transport through an uncharged, 'free water' and charged, 'the electrical double layer' coupled with a chemical equilibrium model for interaction between pore solution and solid phase. A set of modified Poisson-Nernst-Planck equations, including the effect of temperature, pore solution property, and pore structure changes, have been introduced for multi-ionic transport. A comprehensive method has been illustrated for determining the diffusion coefficient at infinite dilution of the aqueous species present in the pore solution in a cementitious material. Numerical predictions were compared to experimental data to demonstrate the applicability of the RTM. For mortar specimens exposed to NaCl solution and seawater, numerical predictions agree well with experimentally determined Portlandite and carbonate in the phase assemblage, elemental distribution such as chloride, sodium, potassium, magnesium, and sulfur adjusting the initial tortuosity factor.